Influence of Various Basin Types on Performance of Passive Solar Still: A Review - Tri Hieu Le; Minh Tuan Pham; H Hadiyanto; Van Viet Pham; Anh Tuan Hoang (Center of Biomass & Renewable Energy, Diponegoro University, 2021)
Passive solar still is the simplest design for distilling seawater by harnessing solar energy. Although it is undeniable that solar still is a promising device to provide an additional freshwater source for global increasing water demand, low thermal efficiency along with daily distillate yield are its major disadvantages. A conventional solar still can produced 2 to 5 L/m2day. Various studies have been carried out to improve passive solar stills in terms of daily productivity, thermal efficiency, and economic effectiveness. Most of the researches that relate to the daily output improvement of passive solar still concentrates on enhancing evaporation or/and condensation processes. While the condensation process is influenced by wind velocity and characteristics of the condensed surface, the evaporation process is mainly affected by the temperature of basin water. Different parameters affect the brackish water temperature such as solar radiation, design parameters (for example water depth, insulators, basin liner absorptivity, reflectors, sun tracking system, etc). The inclined angle of the top cover is suggested to equal the latitude of the experimental place. Moreover, the decrease of water depth was obtained as a good operational parameter, however, the shallow water depth is required additional feed water for ensuring no dry spot existence. Reflectors and sun-tracking systems help solar still absorb as much solar intensity as possible. The internal reflector can enhance daily yield and efficiency of stepped solar still up to 75% and 56% respectively, whereas, passive solar still with the support of a sun-tracking system improved daily yield up to 22%. Despite large efforts to investigate the impact of the different parameters on passive solar distillation, the effect of the basin liner (including appropriate shapes and type of material), needs to be analyzed for improvement in practical utilization. The present work has reviewed the investigation of the solar still performance with various types of basin liner. The review of solar stills has been conducted critically with rectangular basin, fins basin, corrugated basin, wick type, steps shape, and cylindrical shape basin with variety of top cover shapes. The findings from this work conclude that the basin liner with a cylindrical shape had better performance in comparison with other metal types and provides higher freshwater output. Stepped type, inclined, fin absorber, and corrugated shapes had the efficient performance. Further exploration revealed that copper is the best-used material for the productivity of passive solar still.